Tuberculose em necropsias realizadas no Serviço de Anatomia Patológica da Faculdade de Medicina de Botucatu - Joaquim, Andrei Fernandes; Carandina, Luana [UNESP]; Defaveri, Julio [UNESP] (My University, 2006)
Among 6,316 necropsies performed in the period 1969-2000 at the Department of Pathology of Botucatu Medical School UNESP, 240 were of tuberculosis. Among them, 117 were registered as the principal disease (tuberculosis/principal disease group) and 123, as associated to another disease (tuberculosis/ associated disease group). In the tuberculosis-principal disease group, 100% had active tuberculosis, 80 patients were male and 37 were female, with mean age of 47.7 years. Cachexia (37.2%) and cor pulmonale (23.7%) were the most prevalent comorbities in this group. The lungs were affected in 95.7% of the cases, followed by lymph nodes (38.9%) and pleura (27.1%). The morphology and frequency of pulmonary lesions were: 1. miliar: 58.4%; 2. caverns, 56.6%; 3. fibrosis, 41.5%; 4. bronchiectasias, 26.5%; 5. emphysema, 19.4% and 6. cysts, 1.7%. Caverns were observed in different areas of both lungs, with discreet predominance in the right lung, were located mainly in the apices (100%), and the great majority (94%) was bilateral. The others lesions were distributed randomly in both lungs. In the tuberculosis/associated disease group, 70.8% was male, and the two most frequent principal diseases were AIDS (22.1%) and alcoholism (16.3%). Also, the lung was the most affected organ (85.2%), followed by lymph nodes (31.9%) and spleen (28.6%). In 100% of AIDS there were pulmonary lesions. This study in necropsies reinforces epidemiological data that tuberculosis is an important disease, and, also, constitutes an invaluable tool to gather information for a better understanding of the pathology and the epidemiology of tuberculosis in our region.
Tuberculosis in necropsies performed at the Department of Pathology of Botucatu Medical School
Keywords: Epidemiology; Necropsies; Pathology; Tuberculosis